2016
DOI: 10.1002/jmv.24638
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the possibility of arthropod transmission of HCV

Abstract: Hepatitis C virus (HCV) is a major cause of chronic hepatitis, cirrhosis, and liver cancer occurring in up to 3% of the world's population. Parenteral exposure to HCV is the major mode of transmission of infection. Once established, infection will persist in up to 85% of individuals with only a minority of patients clearing viremia. Egypt has possibly the highest HCV prevalence in the world where 10-20% of the general population are infected with HCV. Endemic HCV appears to be concentrated in the tropics and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
7
0
2
Order By: Relevance
“…It is unclear how genes might be transferred to the insect genome from vertebrate viruses, but infection during blood feeding on a contaminated vertebrate host seems to be the most probable route. Recently, the putative role of arthropods in hepatitis virus transmission has been considered (Houldsworth, 2017 ). Hepatitis virus has been found to be stable and viable for at least 1 month in the gut of bed bugs ( Cymex lectularius and C. hemipterus ) and R. prolixus , with the virus being detected in feces and transmitted trans stadially (Blow et al, 2001 ; Silverman et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear how genes might be transferred to the insect genome from vertebrate viruses, but infection during blood feeding on a contaminated vertebrate host seems to be the most probable route. Recently, the putative role of arthropods in hepatitis virus transmission has been considered (Houldsworth, 2017 ). Hepatitis virus has been found to be stable and viable for at least 1 month in the gut of bed bugs ( Cymex lectularius and C. hemipterus ) and R. prolixus , with the virus being detected in feces and transmitted trans stadially (Blow et al, 2001 ; Silverman et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, Hepatitis virus has been detected in mosquitoes in endemic areas, and it has been found that Hepatitis virus efficiently replicates in cultures of mosquito cells (Fallecker et al, 2017 ). The possibility of Hepatitis transmission by arthopods has been hindered by the ignorance of natural reservoirs of the virus or documentation of prevalence of the virus in putative vectors (Houldsworth, 2017 ). In any scenario, the presence of active hepacivirin genes in the R prolixus genome suggests that the interaction between Hepatitis-like virus and insects might be evolutionary old.…”
Section: Discussionmentioning
confidence: 99%
“…HCV-инфекция не передается контактно-бытовым путем. При совместном приеме пищи и укусах насекомых передача парентеральных гепатитов В и С не доказана [10][11][12]. В ходе исследования у большинства респондентов из обеих групп выявлено негативное отношение к больным ХГВ и ХГС, которое проявлялось стремлением исключить бытовые контакты и отказе проживать в одной комнате с больным ХГВ/ХГC и не желании совместного пребывания своего ребенка/брата в одной группе детского сада с больным ХГВ/ХГC ребенком.…”
Section: хронические гепатиты в и с как стигмаunclassified
“…12 Egypt has possibly the highest HCV prevalence in the world where 10%-20% of the general population is infected with HCV. 13 According to the Centers for Disease Control and Prevention (CDC), liver cirrhosis is the 4 th cause of death in Egypt with hepatitis being the 9 th cause. 14 Direct healthcare costs of HCV-related disease exceed $700 million annually and consume approximately 4.0% of the total health expenditure in Egypt, exemplifying the magnitude of the HCV epidemic in Egypt.…”
Section: Liver Fibrosis and Cirrhosis In Hepatitis Cmentioning
confidence: 99%